2013
DOI: 10.1002/bdra.23138
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study using residual newborn dried blood spots to assess the potential role of cytomegalovirus and Toxoplasma gondii in the etiology of congenital hydrocephalus

Abstract: BACKGROUND-Congenital hydrocephalus is a condition characterized by accumulation of cerebrospinal fluid in the ventricles of the brain. Prenatal infections are risk factors for some birth defects. This pilot study investigated whether residual dried blood spots (DBS) could be used to assess infections as risk factors for birth defects by examining the associations between prenatal infection with Toxoplasma gondii (T. gondii) or cytomegalovirus (CMV) with congenital hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Intrauterine infections with enterovirus [21], lymphocytic choriomeningitis [22], CMV and toxoplasmosis [23] have all been associated with hydrocephalus, but their contribution to the total burden of infantile hydrocephalus remains unknown. A recent pilot study [23] found that infants with hydrocephalus were more likely to have evidence of toxoplasmosis or CMV infection on neonatal blood spot cards than infants without hydrocephalus. The odds ratio was not statistically significant, which the authors attributed to reduced sensitivity of stored specimens and to small numbers of affected patients overall.…”
Section: Causes Of Hydrocephalusmentioning
confidence: 99%
“…Intrauterine infections with enterovirus [21], lymphocytic choriomeningitis [22], CMV and toxoplasmosis [23] have all been associated with hydrocephalus, but their contribution to the total burden of infantile hydrocephalus remains unknown. A recent pilot study [23] found that infants with hydrocephalus were more likely to have evidence of toxoplasmosis or CMV infection on neonatal blood spot cards than infants without hydrocephalus. The odds ratio was not statistically significant, which the authors attributed to reduced sensitivity of stored specimens and to small numbers of affected patients overall.…”
Section: Causes Of Hydrocephalusmentioning
confidence: 99%
“…One case-control study suggested an association between CMV or T. gondii and CH, with estimated ORs of 3.78 and 10.6, respectively, for the association. 23 Sexually transmitted disease at the time of delivery was associated with 1.2% of pregnancies in which the infant developed CH according to a cohort study. 27 Nevertheless, none of the identified associations were statistically significant.…”
Section: Congenital Infectionsmentioning
confidence: 99%
“…17 In a case-control study, prenatal CMV and T. gondii infections were considered as risk factors for CH, but these associations did not reach statistical significance. 23 The lack of significance was attributed to the limited number of analyzed samples and their quality, or to the relatively small proportion of cases that is related to these infections. In this context, it is worth noting that a recent study suggests an association between congenital T. gondii infection and specific anatomical patterns of CH, 12 whereas a meta-analysis of fetal ultrasound findings indicates an association between CMV congenital infection and hydrocephalus (in 4.7% of pregnancies).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All three patients with concurrent encephalocele and all eight patients with concurrent myelomeningoceles were also found to have congenital ToRCH infections. 15 Treatment for toxoplasmosis in utero and during the first year of life has been shown to significantly improve outcomes.…”
Section: Resultsmentioning
confidence: 99%